Development and validation of a label-free colorimetric aptasensor based on the HCR and hemin/G-quadruplex DNAzyme for the determination of patulin in fruits and fruit-based products from Xinjiang (China). Issue 35 (17th August 2022) - Lu, Chunxia; Chen, Xia; Ji, Yong; Liu, Chengjiang; Liu, Changbin
Abstract : In this study, a simple and practical label-free colorimetric aptasensor was successfully prepared for the ultrasensitive detection of patulin, based on the hybridization chain reaction and hemin/G-quadruplex DNAzyme-signal amplification strategy. Abstract : In this study, a simple, novel and practical label-free colorimetric aptasensor was successfully prepared for the ultrasensitive detection of patulin, based on the hybridization chain reaction (HCR) and hemin/G-quadruplex DNAzyme-signal amplification strategy. In this aptasensor, a detection probe was designed consisting of the aptamer sequence for the patulin and an initiator sequence to trigger the HCR. Two hairpin structures (H1 and H2) that included the G-quadruplex sequences in inactive configuration were used as functional elements. The presence of patulin triggered the opening of the hairpin structure and the beginning of the HCR. After the addition of hemin, G-rich DNA self-assembled into the peroxidase-mimicking hemin/G-quadruplex DNAzymes, which catalyzed a colorimetric reaction. Under optimized conditions, patulin was measured within a linear range of 0.1–200 ng mL −1, and the detection limit was 0.060 ng mL −1 . The recovery rates ranged from 91.4 to 105% for fruits and fruit-based products. Subsequently, a total of 311 samples comprising fruits, fruit-based products and dried fruits were collected from supermarkets, production bases and farmers' markets in Xinjiang, and analyzed for patulin using the proposed aptasensor. Patulin was detected in 16 samples (5.14%) at concentrations ranging from 1.23 to 16.4 μg kg −1 . None of the samples exceeded the maximal level set by the EU commission (50 μg kg −1 ). The positivity in fresh fruits (7.69%) was significantly higher than that of fruit-based products (4.00%) and dried fruits (1.25%). In summary, the proposed aptasensor can quickly detect patulin in food samples, thus providing a warning for mycotoxin contamination.